2014
DOI: 10.1039/c4ra01857e
|View full text |Cite
|
Sign up to set email alerts
|

Double-walled TiO2nanotubes prepared with NH4BF4based electrolyte and their photoelectrochemical performance

Abstract: Anodic DW-TiO2 NTs and SW-TiO2 NTs are prepared in NH4BF4 based electrolyte and their formation can be tuned by voltages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Highly ordered MR-TNTs were rstly prepared by a two-step anodization method 24,25 and then reduced by NaBH 4 aqueous solution with microwave assistance (Scheme 1).…”
Section: Preparation Of Self-doped Mr-tntsmentioning
confidence: 99%
“…Highly ordered MR-TNTs were rstly prepared by a two-step anodization method 24,25 and then reduced by NaBH 4 aqueous solution with microwave assistance (Scheme 1).…”
Section: Preparation Of Self-doped Mr-tntsmentioning
confidence: 99%
“…The mechanisms for the formation of DW-TiO 2 NTs and SW-TiO 2 NTs for the PEC reaction prepared at various anodizing parameters (time, voltage, temperature, etc.) in the different IL-based electrolytes were recently discussed in the literature [13,[65][66][67][68][69][70][71][72]. The mechanisms can be described for the decomposition of the anion [BF 4 ] − to release fluoride ions into the electrolyte under the high energy field [66].…”
Section: Nanostructured Semiconductor For the Pec Ws Reactionmentioning
confidence: 99%
“…In addition to aforementioned positive effects on the photocatalytic degradation of pollutes, Schmuki et al reported that the double‐walled structure could improve the thermal stability of TiO 2 nanotube array. Li et al also found that the double‐walled TiO 2 nanotube array demonstrated the potential of improving photoconversion efficiency in photoelectrochemical water splitting. Therefore, one could expect that the tube wall modulation can open a new avenue for enhancing applications of anodic metal oxide nanotube arrays.…”
Section: Introductionmentioning
confidence: 99%